Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis